2013
DOI: 10.1002/0471142700.nc0512s54
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interstrand Cross‐Link Formation Using Furan as a Masked Reactive Aldehyde

Abstract: This unit describes a method for interstrand cross-linking between a furan-modified oligonucleotide and its unmodified complement. The synthesis of two furan-modified phosphoramidites, selected based on high cross-linking yield versus improved cross-linking selectivity, is described. The methods allow gram-scale synthesis starting from stable and readily available furan derivatives. Cross-linking requires selective oxidation of the furan moiety to an aldehyde. The masked nature of the latter avoids undesired a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…It should be noted that the relative reactivity of the nucleobase reflects their true reactivities as they were compared under the same conditions without complication from the base‐pairing/stacking ability of different nucleobases. Nevertheless, the reactivity pattern of C and A towards crosslinking with furan is in line with other studies [1a,21,23a,24,25,29,34] . Remarkably, the G base was for the first time found to participate in the crosslinking reaction with furan.…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the relative reactivity of the nucleobase reflects their true reactivities as they were compared under the same conditions without complication from the base‐pairing/stacking ability of different nucleobases. Nevertheless, the reactivity pattern of C and A towards crosslinking with furan is in line with other studies [1a,21,23a,24,25,29,34] . Remarkably, the G base was for the first time found to participate in the crosslinking reaction with furan.…”
Section: Discussionsupporting
confidence: 91%
“…Our group therefore started exploring the use of furan moieties as masked aldehydes for a novel cross-linking technology. [55][56][57][58][59][60][61][62][63][64][65][66][67] Owing to the stability of the furan moiety before oxidation, a large series of furan derivatives is readily available. Moreover, the moiety is compatible with most of the standard chemistries used for modified nucleoside, amino acid, ODN and peptide synthesis.…”
Section: A Maddermentioning
confidence: 99%
“…1). [18][19][20][21][22] We have shown that furan moieties can be easily incorporated in oligodeoxynucleotides (ODNs) in view of the stability and wide commercial availability of furan derivatives. Furan modified ODNs can be activated by oxidation to a very reactive oxo-butenal that quickly reacts with the exocyclic amine of the opposite base resulting in selective and high yielding interstrand cross-link (ICL) formation.…”
Section: Introductionmentioning
confidence: 99%